Do Trichoptera in running water fly upstream? - Larsson, Malin (Linköpings universitet, Biologi, 2015)
Drift moves aquatic insects downstream, risking depopulation of upstream reaches. However, the necessity and existence of an upstream flight to compensate for drift has not been undisputed. I analysed a sample of approximately 70 000 Trichoptera from a stream in northern Sweden collected during one season in 1974. The overall flight direction was upstream. Females had a stronger upstream flight than males and species varied in both flight direction and strength of the preference. Flight direction was not affected by wind or trap type. Upstream flight varied during the season and with different larval behaviours. Upstream flight increased with the size of the imago and with the abundance in flight. A colonisation cycle might be in effect but even though upstream flight occurs, it might not be necessary to sustain populations in upstream reaches.